How do you solve 2( m + 3) = - ( 4m + 12)?

Feb 2, 2017

$m = - 3$

Explanation:

$2 \left(m + 3\right) = - \left(4 m + 12\right)$

$\therefore 2 m + 6 = - 4 m - 12$

$\therefore 2 m + 4 m = - 6 - 12$

$\therefore 6 m = - 18$

$\therefore m = - \frac{18}{6}$

$\therefore m = - 3$

sustitute m$= - 3$

$2 \left(\left(- 3\right) + 3\right) = - \left(4 \left(- 3\right) + 12\right)$

$2 \times 0 = - \left(- 12 + 12\right)$

$2 \times 0 = - \left(0\right)$

$0 = 0$

Feb 2, 2017

The answer is $m = - 3$.

Explanation:

Let's focus first on the left side of the equation. Multiply 2 by both $m$ and $3$. The equation becomes...
$2 m + 6 = - \left(4 m + 12\right)$ .

Now on to the right side, multiply that "$-$" or the negative sign to both $4 m$ and $12$. Think of it as multiplying $- 1$ to those numbers. The equation becomes...
$2 m + 6 = - 4 m - 12$ .

It is time to combine like terms. First, we add $4 m$ to both sides of the equation.
$4 m + 2 m + 6 = - 4 m - 12 + 4 m$.

On the left side of the equation, add $4 m$ and $2 m$. On the right side, adding $4 m$ and $- 4 m$ cancels each other out, that is, the answer is equal to $0$. The equation becomes...
$6 m + 6 = - 12$.

Now, we'll subtract $6$ on both sides of the equation. It is similar to the previous step but we are subtracting instead. The equation becomes...
$6 m = - 18$.

Simplify the equation by dividing 6 on both sides. Divide the like terms and leave out the $m$ since it is a variable, not a number. The solution goes like this:
$\left(\frac{6 m}{6}\right) = \left(\frac{- 18}{6}\right)$.

The answer is now $m = - 3$. Hope this helps you.